Existing and emerging methods of diagnosis and monitoring of pediatric musculoskeletal infection. Issue 10 (October 2020) - Michalowitz, Andrew; Yang, Jenny; Castaneda, Pablo; Litrenta, Jody
Highlights: Pediatric musculoskeletal infection is evolving to include both more complex pathologies and more virulent pathogens. Advanced imaging, such as MRI, provides valuable and detailed information regarding the complexity of these pathologies, which directly translates to clinical benefits. Future techniques, such as genome sequencing, are likely to gain momentum to improve the likelihood and speed of detection of pathogens. Abstract: Methods of diagnosing and monitoring pediatric musculoskeletal infections are rapidly evolving. Key serologic tests are typically used in screening patients with suspected infections, and remain an integral part of the initial work-up. Synovial studies from arthrocentesis in possible septic arthritis, and source-specific cultures have been the foundation of our treatment algorithm. Given the prevalence of soft tissue abscesses and osteoarticular infections, advanced imaging is an advantageous tool. More affordable use and expanded access to MRI has made it a valuable adjunct to clinical picture and existing tests in order to comprehensively visualize the extent of musculoskeletal infections in children. Ongoing validation for criteria to help determine the patients that stand to benefit the most from MRI, even when surgical intervention may be delayed, remains of significant clinical interest. Given the rates of culture-negative infections, and the need for timely diagnosis, new diagnostic techniques are always being considered. The search for more accurate biomarkers, and technology such as Whole genome sequencing (WGS) and next-generation sequencing (NGS) that can rapidly identify pathogens of all types of phyla based on a small sample of DNA, has promising clinical implications. While once novel and prohibitively expensive, these tests are now being applied in university and tertiary care centers in certain scenarios. Applying these techniques to pediatric musculoskeletal will require a large change in lab workflow and training. However, the benefits of acquiring diagnostic information along with will make them a superior tool in our arsenal of diagnostic tests.